The determinants of private savings in Turkey: The role of financial development - Selçuk Akçay (Economic Journal of Emerging Markets, 2023)
Purpose ― Over the past two decades since the 2000s, Turkey's private savings rates have decreased, which has become a concern for policymakers. In addition to considering the key determinants of private savings, this study primarily aims to quantify the linear and nonlinear impacts of financial development on private savings from 1980 to 2015. Method ― This study uses Autoregressive Distributed Lag (ARDL) procedure and the Fourier Toda-Yamamoto causality framework. Findings ― The main findings are as follows: 1) The ARDL bounds test supports the presence of a long-run equilibrium relationship between private savings and its determinants; 2) Financial development affects private savings nonlinearly in an inverted U-shaped pattern, and 3) No causality relationship is observed between private savings and financial development. Implication ― As financial development has an inverted U-shaped relationship with private savings, indicating that the complementary effect of financial development is replaced with a substitution effect after a certain threshold level, Turkish authorities should consider this evidence when tailoring policies regarding financial markets. Originality ― This study is the first to identify whether the relationship between private savings and financial development is linear or nonlinear in the context of an emerging economy in Turkey.